2020
DOI: 10.3390/jpm10040219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tumor LINE-1 Methylation Level and Neoadjuvant Treatment and Its Association with Colorectal Cancer Survival

Abstract: Recent studies suggest that long-interspersed nucleotide element-1 (LINE-1) hypomethylation is commonly found in colorectal cancer (CRC), and is associated with worse prognosis. However, the utility of LINE-1 methylation on the prognosis of CRC is still controversial, and may be due to the fact that some clinical and pathological features may affect LINE-1 methylation. Thus, the aim of this study was to assess the prognostic value of tumor LINE-1 methylation in CRC, through their association with the CRC clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…LINE-1 is more hypomethylated in CRC tumors compared with adjacent normal tissue, and this is linked to metastasis. Moreover, LINE-1 is more hypermethylated in the neoplastic tissue of patients treated for CRC compared with untreated patients, and after neoadjuvant treatment, poor survival was observed in patients with tumor LINE-1 hypomethylation[ 26 ]. The results of a meta-analysis also support the idea that LINE-1 hypomethylation is considerably associated with the shortened OS and disease-free survival (DFS) of patients with CRC[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…LINE-1 is more hypomethylated in CRC tumors compared with adjacent normal tissue, and this is linked to metastasis. Moreover, LINE-1 is more hypermethylated in the neoplastic tissue of patients treated for CRC compared with untreated patients, and after neoadjuvant treatment, poor survival was observed in patients with tumor LINE-1 hypomethylation[ 26 ]. The results of a meta-analysis also support the idea that LINE-1 hypomethylation is considerably associated with the shortened OS and disease-free survival (DFS) of patients with CRC[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bachitta et al (82) conducted a meta-analysis in 2014, which described the role of LINE-1 hypomethylation in human cancer. It has also been shown that LINE-1 hypomethylation in CRC was associated with poor prognosis, survival and advanced stage, and that it could be a prognosis predictor of CRC (83,84). In addition to its prognosis value, a recent study reported that LINE-1 hypomethylation was effective in the early detection of CRC (85).…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
“…Previous research indicates that LINE-1 methylation in CRC adenomas is associated with polyp size and dysplasia severity. Therefore, low methylation and high expression of LINE-1 are conjectured to be associated with negative prognosis in CRC patients, with almost no heterogeneity in LINE-1 methylation within tumors [ 68 , 69 , 70 ]. Consequently, the combination of the fecal immunochemical test (FIT) with methylation biomarkers and low methylation of LINE-1 may enhance the sensitivity of screening and prognosis in CRC patients.…”
Section: Methylationmentioning
confidence: 99%